Characterisation of the in vivo interactions between detomidine and methadone in horses: Pharmacokinetic and pharmacodynamic modelling - Gozalo-Marcilla, M. [UNESP]; Luna, S. P.L. [UNESP]; Moreira da Silva, R.; Crosignani, N. [UNESP]; Lopes, N. P.; Taylor, P. M.; Pelligand, L. (Wiley, 2019)
Background: Pharmacokinetic (PK)/pharmacodynamic (PD) modelling offers new insights to design protocols for sedation and analgesia in standing horses. Objectives: To evaluate the parameters and interactions between detomidine and methadone when given alone or combined in standing horses. Study design: Randomised, placebo-controlled, blinded, crossover. Methods: Eight adult healthy horses were given six treatments intravenously: saline (SAL); detomidine (5 μg/kg bwt; DET); methadone (0.2 mg/kg bwt; MET) alone or combined with detomidine (2.5 [MLD], 5 [MMD] or 10 [MHD] μg/kg bwt). Venous blood samples were obtained at predetermined times between 0 and 360 min after drug administration. Plasma detomidine and methadone were measured using a single, liquid/liquid extraction technique by liquid chromatography coupled with a triple quadrupole mass spectrometer (LC-MS/MS). Sequential PK/PD modelling compared rival models, with and without PK and PD interaction between drugs, to fit the PD data including height of the head above the ground (HHAG), a visual analogue scale for sedation (VAS), electrical (ET), thermal (TT) and mechanical (MT) nociceptive thresholds and gastrointestinal motility (GIM) [1]. Results: Two and three compartment models best described the PK of detomidine and methadone, respectively. Detomidine decreased its own clearance as well as the clearance of methadone. The interaction of methadone on the effect of detomidine revealed an infra-additive (partial antagonism) effect for HHAG (α = −1.33), VAS (α = −0.98) and GIM (α = −1.05), a positive potentiation for ET (pot = 0.0041) and TT (pot = 0.133) and a synergistic to additive effect for MT (α = 0.78). Main limitations: This is a small experimental study. Conclusions: Different PK/PD interactions were demonstrated for each PD parameter and could be modelled in vivo. The modelling of our data will allow us to simulate and predict the effect of constant rate infusions of both drugs for future investigations.
Keywords: alpha 2 agonist; horse; nociceptive threshold; opioid; sedation; synergism